2021
DOI: 10.1186/s40900-021-00331-9
|View full text |Cite
|
Sign up to set email alerts
|

Reporting of patient and public involvement and engagement (PPIE) in clinical trials published in nursing science journals: a descriptive study

Abstract: Background Patient and Public Involvement and Engagement (PPIE) in research positively affects the relevance, quality, and impact of research. Around 11% of studies published in leading medical journals demonstrate PPIE. The extent of PPIE in nursing research has not been previously studied. Methods A descriptive study of PPIE in clinical trials published in general nursing science journals between 1st January and 31st August 2021. Data were extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 11 publications
2
11
0
Order By: Relevance
“…Second, the online survey in Stage 1 (Orientation) allowed for detailed insights into the status quo of PPIE in pediatric oncology across Europe to understand knowledge, approaches, and attitude of both HCP and patients equally. In line with prior research looking into the currently practiced degree of involvement, 9,18,21 extensive deficits in the establishment of PPIE came to light. Thereby significantly more patients stated to never have been involved in any type of scientific research while HCPs claimed to involve patients significantly more in the later research steps.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Second, the online survey in Stage 1 (Orientation) allowed for detailed insights into the status quo of PPIE in pediatric oncology across Europe to understand knowledge, approaches, and attitude of both HCP and patients equally. In line with prior research looking into the currently practiced degree of involvement, 9,18,21 extensive deficits in the establishment of PPIE came to light. Thereby significantly more patients stated to never have been involved in any type of scientific research while HCPs claimed to involve patients significantly more in the later research steps.…”
Section: Discussionmentioning
confidence: 64%
“…The derived workflow (Figure1) can therefore serve as framework and practical guidance for future projects aiming at implementing PPIE, since it highlights necessary elements of participation, engagement, and involvement and allows for the individual adaptation to the specific circumstances of future research.Second, the online survey in Stage 1 (Orientation) allowed for detailed insights into the status quo of PPIE in pediatric oncology across Europe to understand knowledge, approaches, and attitude of both HCP and patients equally. In line with prior research looking into the currently practiced degree of involvement,9,18,21 extensive deficits in the establishment of PPIE came to light. Thereby significantly more patients stated to never have been involved in any type of scientific research while HCPs claimed to involve patients significantly more in the later research steps.…”
mentioning
confidence: 55%
“… 15 Although the authors of these studies did not attempt to measure the proportion of published papers involving PPI, as we have done here, they uniformly identified few studies reporting PPI within the large literatures in which they were interested; a study of clinical trials published in nursing journals failed to find any evidence of PPI. 35 We know of only one recent study on the prevalence of PPI in general medical research, which, in a smaller sample, found that 11% of papers reported PPI inclusion. 36 We are unaware of any other studies on the prevalence of PPI inclusion or of factors associated with it.…”
Section: Discussionmentioning
confidence: 98%
“…Parents of children with ABI have been involved in the design of this protocol to seek advice on the relevance of the topic and the study approach. 13 Amendments were made to include parental experiences of different conditions associated with ABI, such as TBI or brain tumours, as parents perceived the experience may be different across various types of ABI.…”
Section: Methods and Analysismentioning
confidence: 99%